Higher vasoactive usage despite hemodynamic goals is associated with higher mortality in acute myocardial infarction-related cardiogenic shock - Ortega-Hernández, Jorge A.; González-Pacheco, Héctor; Araiza-Garaygordobil, Diego; Gopar-Nieto, Rodrigo; Sierra-Lara-Martínez, Daniel; Manzur-Sandoval, Daniel; Briseño-De-La-Cruz, José Luis; Mendoza-García, Salvador; Montañez-Orozco, Álvaro; Arzate-Ramírez, Arturo; Arenas-Díaz, José Omar; Gómez-Rodríguez, César A.; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiogenic shock (CS) is a severe complication of acute myocardial infarction (AMI) with high mortality. Few studies have examined the selection and subsequent choice of vasoactive agents in CS. This study investigates the impact of vasoactive drug use and in-hospital outcomes among AMI-CS.Materials and methodsA total of 309 patients who underwent pulmonary artery catheterization between 2006 and 2021 were categorized by the number of vasoactive drugs used (0–1, 2, or >2). Clinical and 24 h hemodynamic data were analyzed. Primary outcomes explored the correlation between vasoactive use and in-hospital mortality. Secondary analyses assessed hemodynamic changes and estimated mortality probabilities at different intervals using logistic regression.ResultsIn total, 57 patients received 0–1, 76 received 2, and 176 received >2 vasoactive drugs. The median age was 61 years; most were men (82%), and 82.8% had ST-segment elevation myocardial infarction. End-organ function showed progressive deterioration with escalating vasoactive use. Survival analysis revealed an increased mortality in the >2 vasoactive group [HRadj = 4.62 (2.07–10.32)], achieving ≥5/6 hemodynamic goals that did not mitigate mortality [HRadj = 7.18 (1.59–32.39)]. Subgroup analyses within patients who reached different hemodynamic goals reiterated adverse outcomes associated with >2 vasoactives (P < 0.05). Further analysis showed that vasopressin was associated with the highest mortality in a time-dependent fashion [HRDay1, 8.77 (6.04–12.75) → HRDay30, 1.23 (0.8–1.87)], and levosimendan had similar behavior [HRDay1, 2.67 (1.82–3.91) → HRDay30, 0.66 (0.42–1.03)].ConclusionsA significant association between the number of vasoactives and in-hospital mortality was found in AMI-CS, which requires future long-term studies to explore the role of vasoactive drug therapies and early temporary mechanical circulatory support.